ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Trisnaningsih, Sri; Saputri, dan Yudiyani (Journal of Accounting and Strategic Finance, 2009)
This research is useful to test the ability of Liquidity ratio (CR, WCTA, SA), Profitability (ROI, ROE, NPM) and Financial Leverage (DR) in predicting the probability of financial distress at the condition of manufacturing firms in Indonesia Stock Exchange. This sample amounted to 49 companies consisting of the observation period 2007-2008 in which 44 companies that have non-financial conditions of distress and 5 companies that experience financial distress. Period estimates in this study is the year 2005 until 2007. This research is based on a quantitative approach using group membership prediction techniques, which are statistically test the research hypothesis is done by using logistic regression Backward Stepwise method with the help of SPSS. The results of this study indicate that financial ratios can be used to predict the financial distress condition at the manufacturing companies in Indonesia Stock Exchange. This is based on the level of accuracy shown in Clasification overall rate of 98.0%. However, the results of this study also shows that not all financial ratios that can be used to predict the financial distress condition of corporate. The ratio of the dominant in explaining the financial distress condition of corporate is profitability ratios that are proxies by the ROI. Keywords: financial distress, financial ratios, logistic regression.